2023
DOI: 10.58777/mbs.v1i1.152
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of In-Store Logistics Performance, Store Image, Sales Promotion, and Service Quality on Customer Satisfaction

Yulia Kartika Sari,
Ariel Nian Gani,
Nazma Riska Zhafiraah

Abstract: The purpose of this study is to determine the effect of In-Store Logistics performance, Store Image, Sales Promotion, and Service Quality on Matahari Department Store Consumers. The population in this study is Matahari Department Store consumers in Mal Artha Gading. The sampling technique used is purposive sampling. The number of respondents in this study was 100 respondents. Data was collected by distributing questionnaires. The data analysis methods used are multiple regression analysis, t-test (partial), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Conversely, if customers feel that a particular product or service is not worth the price, they will not repeat the purchasing behavior. These results are in accordance with Service Quality Price Patient Satisfaction previous research conducted by Bramtika et al (2019) and Sari et al (2023), which shows that the price variable influences the consumer satisfaction variable. This finding is supported by research conducted by Anam, et al (2019) that price has a positive influence on patient satisfaction.…”
Section: Research Hypothesissupporting
confidence: 92%
“…Conversely, if customers feel that a particular product or service is not worth the price, they will not repeat the purchasing behavior. These results are in accordance with Service Quality Price Patient Satisfaction previous research conducted by Bramtika et al (2019) and Sari et al (2023), which shows that the price variable influences the consumer satisfaction variable. This finding is supported by research conducted by Anam, et al (2019) that price has a positive influence on patient satisfaction.…”
Section: Research Hypothesissupporting
confidence: 92%
“…An effective marketing strategy helps IKM understand the needs of consumers and their markets so they are able to develop relevant and appropriate marketing actions. Through creative and innovative marketing strategies, SMEs can differentiate themselves from competitors, create positive experiences for consumers, and strengthen relationships with them (Sari et al, 2023). Responsiveness to consumer needs and continuous evaluation of marketing performance is the key to increasing consumer satisfaction and sustainably developing SMEs.…”
Section: Marketing Strategy and User Satisfactionmentioning
confidence: 99%
“…The Influence of Service Quality on Customer Satisfaction Hardiansyah (2011) found out the quality of service that consumers actually feel; there are indicators of service quality that lie in five factors that determine the quality of a service, including tangibility, responsiveness, guarantee, and empathy. Supriyadi et al (2017) and (Sari et al, 2023) concluded that tangibles are physical facilities, equipment, employees, office font space, available parking space, and employee appearance. The company provides its services right the first time (Diza et al, 2016).…”
Section: Research Hypothesismentioning
confidence: 99%